Transit Migration in Europe (Taylor & Francis, 2025)
Transit migration, comprising mixed flows of refugees and labour, is widely considered a concern and even security threat. However, the concept is as vague and blurred as it is politicised. This volume offers evidence-based, comprehensive coverage of the entire belt of countries in the neighbourhood of the EU, ranging from Russia to Morocco. Transit migration is critically analyzed from the perspective of sending, transit and receiving countries, offering new insights into refugee and irregular migration flows, transnational migration networks and overlapping migration systems.